Experimental Yellow Fever in Squirrel Monkey: Characterization of Liver In Situ Immune Response - Milene S. Ferreira; Jorge R. Sousa; Pedro S. Bezerra Júnior; Valíria D. Cerqueira; Carlos A. Oliveira Júnior; Gabriela R. C. Rivero; Paulo H. G. Castro; Gilmara A. Silva; José Augusto P. C. Muniz; Eliana V. P. da Silva; Samir M. M. Casseb; Carla Pagliari; et al. (Viruses, 2023)
Non-human primates contribute to the spread of yellow fever virus (YFV) and the establishment of transmission cycles in endemic areas, such as Brazil. This study aims to investigate virological, histopathological and immunohistochemical findings in livers of squirrel monkeys (Saimiri spp.) infected with the YFV. Viremia occurred 1–30 days post infection (dpi) and the virus showed a predilection for the middle zone (Z2). The livers were jaundiced with subcapsular and hemorrhagic multifocal petechiae. Apoptosis, lytic and coagulative necrosis, steatosis and cellular edema were also observed. The immune response was characterized by the expression of S100, CD11b, CD57, CD4 and CD20; endothelial markers; stress and cell death; pro and anti-inflammatory cytokines, as well as Treg (IL-35) and IL-17 throughout the experimental period. Lesions during the severe phase of the disease were associated with excessive production of apoptotic pro-inflammatory cytokines, such as IFN-γ and TNF-α, released by inflammatory response cells (CD4+ and CD8+ T lymphocytes) and associated with high expression of molecules of adhesion in the inflammatory foci observed in Z2. Immunostaining of the local endothelium in vascular cells and the bile duct was intense, suggesting a fundamental role in liver damage and in the pathogenesis of the disease.